Study on Kinetics of Growth and Weight of Vanadium Gel on Short-Circuited Probes from Various Materials - Sulejmenov Esen Nurgalyevich; Utelbayeva Akmaral Bolysbekovna; Meldeshov Amangeldy Abdychalikovich; Romanteyev Yuri Pavlovich; Utelbayev Bolysbek Toychibekovich (Recent Trends in Chemical and Material Sciences Vol. 2, 2021)
Development of technological processes in chemical and metallurgy industry is a significant increased in research chemical systems with a view their practical application. The article provides results of experiments on research of speed of escalating of vanadium gel on short-circuited probes from various metals, particularly from copper and aluminium it is shown that speed of escalating of gel on probes is influenced with a material of a probe and configuration of probes in a solution. Research of growth of vanadic gel on metal probes from various metals allows to draw a conclusion on the electrochemical nature of this process. Formation of vanadic mesogels can be considered as macroscopically manifestation of processes of self-organizing which spontaneously proceed in a solution.